NON-SURGICAL MANAGEMENT OF CHRONIC RADICULAR PAIN IN LUMBAR CANAL STENOSIS: A CASE REPORT ON THE EFFICACY OF PULSED RADIOFREQUENCY - Aprilia, Arvidareyna Panca; Kurniawan, Shahdevi Nanda (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Low back pain (LBP) is a prevalent condition, particularly in adults aged 40 to 80 years, and is often associated with lumbar canal stenosis. This condition leads to nerve compression, causing radicular pain that radiates to the lower extremities. Non-surgical options such as Pulsed Radiofrequency (PRF) have emerged as effective treatments for patients with chronic radicular pain who do not respond to conservative therapy. Case: We report a case of a 49-year-old female presenting with a three-year history of progressively worsening LBP, radiating to both legs. MRI revealed mild lumbar canal stenosis and posterior listhesis grade I at L3-L4, with bilateral nerve root compression at L4-L5 and S1. Conservative therapy, including physical therapy and pharmacological treatment, provided minimal relief. PRF therapy was subsequently applied to the L4-L5 and S1 nerve roots, resulting in significant pain reduction (NRS 7-8 to 5-6) and improved function. Discussion: Lumbar canal stenosis often leads to neurogenic claudication and radicular pain due to nerve compression. Posterior listhesis exacerbates this condition by contributing to spinal instability. PRF offers a minimally invasive alternative to surgery, with studies showing its efficacy in modulating nociceptive pathways and reducing pain. In this case, PRF effectively reduced pain and improved mobility, offering a safe and efficient treatment option. Conclusion: PRF is an effective non-surgical intervention for managing chronic radicular pain due to lumbar canal stenosis. Its integration into chronic low back pain management protocols and patient education offers significant benefits.